Environmentally friendly transfer adhesive and preparation method and application thereof
Environmental transfer glue prepared by the hydraulic hydrogen aggregation process, the problem of the existing laser transfer coating technology is not environmentally friendly and the effect of poor mold pressure, and the efficient and environmentally friendly laser transfer coating preparation has been achieved. Moving effect.
Patent Information
- Application Number
- CN202211648310.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing laser transfer coating technology has problems such as uneco-friendly and poor molding effect.
Preparation of an environmentally friendly metastatic glue through hydraulic hydrogen aggregation process. It uses high -acid solid acrylic resin and low -dose emulsifier, combined with acrylic monomer, cause, cross -linking agent, and membrane assistant to form a superior film formation. Sexual and tough coating.
The preparation of environmentally friendly metastasis has a good membrane level, toughness, and heat resistance, can achieve the ideal mold pressure effect, reduce production costs and improve the environmental protection of the process.
Smart Images

Figure BDA0004010762900000041 
Figure BDA0004010762900000042 
Figure BDA0004010762900000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer synthetic materials, and in particular to an environmentally friendly transfer adhesive and a preparation method and application thereof. Background Art
[0002] Laser transfer coating is the most important part of laser pattern embossing transfer technology, which determines the effect of electroplated aluminum laser hot stamping products. At present, this technology is mainly used in packaging products such as cigarette labels, wine labels, drug labels, and high-end books and periodicals. The structure of electroplated aluminum laser hot stamping is roughly as follows from top to bottom: glue layer, aluminum layer, information layer, centrifugal layer, base film, and laser transfer coating is the information layer. The resin coating (transfer glue) as the information layer needs to have good film flatness and certain toughness, and can be separated from the base film and have a certain adhesion to the aluminum layer. It must also have properties such as heat resistance, scratch resistance, and corrosion resistance.
[0003] At present, the more mature products on the market are mainly based on solvent-based resins, which have disadvantages such as being environmentally unfriendly and having certain safety hazards; at the same time, there is also the problem of poor molding effect. Summary of the invention
[0004] In order to overcome the problems of the existing technology that the laser transfer coating is not environmentally friendly and has poor molding effect, the first aspect of the present invention provides a transfer adhesive, the second aspect of the present invention provides a method for preparing the transfer adhesive, and the third aspect of the present invention provides an application of the transfer adhesive. Through the aqueous acrylic emulsion polymerization process, the transfer adhesive used for the laser transfer coating has good film flatness and certain toughness, and at the same time has good heat resistance and can achieve an ideal molding effect. Compared with existing similar products, the transfer adhesive of the present invention has the advantages of simple and mature production process, low cost and environmental protection.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The first aspect of the present invention provides a transfer adhesive, wherein the raw materials for preparing the transfer adhesive include the following components in parts by weight:
[0007] 45-65 parts of water, 8-18 parts of solid acrylic resin, 3-5 parts of ammonia water, 0.2-0.6 parts of emulsifier, 25-45 parts of acrylic monomer, 2-5 parts of initiator solution, 0.2-2 parts of crosslinking agent, 1-5 parts of film-forming aid;
[0008] The solid acrylic resin has an acid value of 140 to 280 mg KOH / g and a Tg of 50 to 150°C.
[0009] The solid resin used in the present invention has strong wrapping, good stability, excellent film-forming property, and certain adhesion to the aluminum layer; the emulsifier used can improve the conversion rate of the reaction and improve the stability of the emulsion; the cross-linking agent used can improve the strength of the emulsion after film formation, so that the coating maintains toughness; the film-forming property of the emulsion can be significantly improved by adding a film-forming aid, which can well solve the problem of brittleness of acrylic emulsion with high glass transition temperature. When the environmentally friendly transfer adhesive prepared by the above raw materials is used for laser transfer coating, it has excellent stability, the coating formed by coating is flat and tough, and has good heat resistance, and can achieve an ideal molding effect.
[0010] Preferably, the raw materials for preparing the transfer adhesive include the following components in parts by weight:
[0011] 50-60 parts of water, 10-15 parts of solid acrylic resin, 3-5 parts of aqueous ammonia, 0.3-0.6 parts of emulsifier, 25-40 parts of acrylic monomer, 2-4 parts of initiator solution, 0.2-2 parts of crosslinking agent, 2-5 parts of film-forming aid.
[0012] Preferably, in the raw material for preparing the transfer adhesive, the weight average molecular weight of the solid acrylic resin is 4000-30000; further preferably, the weight average molecular weight of the solid acrylic resin is 5000-20000.
[0013] Preferably, in the raw material for preparing the transfer adhesive, the acid value of the solid acrylic resin is 150 to 260 mg KOH / g; more preferably, the acid value of the solid acrylic resin is 160 to 250 mg KOH / g.
[0014] Preferably, in the raw material for preparing the transfer adhesive, the Tg of the solid acrylic resin is 55-140°C; more preferably, the Tg of the solid acrylic resin is 60-130°C.
[0015] The present invention selects solid acrylic resin with specific weight average molecular weight, acid value and Tg, which has strong encapsulation and can make acrylic monomer react well during emulsion polymerization. The formed emulsion has good stability, good film-forming property after film formation and certain adhesion to the aluminum layer.
[0016] The ammonia water used in the present invention is industrial ammonia water, and the effective concentration is 22-25%. The industrial ammonia water of this concentration is economical and practical, and the moderate concentration can stabilize the pH value of the emulsion.
[0017] Preferably, in the raw material for preparing the transfer adhesive, the emulsifier is an anionic emulsifier; specifically, the emulsifier is selected from at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfate (EO: 2-5). The present invention uses a small amount of anionic emulsifier to enable the hydrophilic monomer to better participate in the reaction, thereby improving the conversion rate of the reaction. The presence of a small amount of emulsifier also improves the stability of the emulsion and effectively reduces the odor of the emulsion.
[0018] Preferably, in the raw materials for preparing the transfer adhesive, the acrylic monomer is a combination of a soft monomer and a hard monomer; the soft monomer includes at least one of methyl acrylate, ethyl acrylate, butyl methacrylate, butyl acrylate, isooctyl methacrylate, isooctyl acrylate, dodecyl acrylate, octadecyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, hydroxybutyl methacrylate, and isobornyl acrylate; the hard monomer includes at least one of styrene, methyl styrene, methyl methacrylate, isobornyl methacrylate, and ethyl methacrylate.
[0019] Preferably, in the raw materials for preparing the transfer adhesive, the copolymer Tg of the acrylic monomer is -5 to 10°C.
[0020] Preferably, in the raw material for preparing the transfer adhesive, the initiator solution is a thermal decomposition type free radical initiator; further preferably, the initiator solution is an aqueous solution of ammonium persulfate and / or potassium persulfate; the concentration of the initiator solution is 5 to 30 wt%.
[0021] Preferably, in the raw materials for preparing the transfer adhesive, the crosslinking agent includes at least one of ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, N-hydroxymethyl acrylamide, and N,N'-methylenebisacrylamide.
[0022] Preferably, in the raw materials for preparing the transfer adhesive, the film-forming aid includes at least one of ethylene glycol monobutyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol methyl ether, propylene glycol vinyl acetate, and dipropylene glycol methyl ether.
[0023] The second aspect of the present invention provides a method for preparing the transfer adhesive, comprising the following steps:
[0024] (1) adding water, solid acrylic resin and emulsifier into a reaction vessel, stirring, adding ammonia water and heating;
[0025] (2) 50-70% of the initiator solution is added into the reaction container at one time, the acrylic monomer and the crosslinking agent are mixed and then the remaining initiator solution is added dropwise into the reaction container respectively, and the mixture is kept warm for 0.5-1.5 hours, and the film-forming agent is added after cooling, and the transfer adhesive is obtained by stirring.
[0026] Preferably, in the preparation method of the transfer adhesive, in step (1), the stirring speed is 80 to 150 r / min.
[0027] Preferably, in the preparation method of the transfer adhesive, in step (1), the heating temperature is 80-90°C; more preferably, the heating temperature is 82-87°C.
[0028] Preferably, in the method for preparing the transfer adhesive, in step (2), 55-65% of the initiator solution is added to the reaction container at one time; further preferably, in step (2), 57-62% of the initiator solution is added to the reaction container at one time.
[0029] Preferably, in the preparation method of the transfer adhesive, in step (2), the insulation temperature is 80-90°C.
[0030] Preferably, in the preparation method of the transfer adhesive, in step (2), the temperature is lowered to room temperature.
[0031] Preferably, in the preparation method of the transfer adhesive, in step (2), the film-forming aid is added and stirred for 20-40 minutes to obtain the transfer adhesive.
[0032] Preferably, in the preparation method of the transfer adhesive, in step (2), the acrylic monomer and the cross-linking agent are mixed and then the remaining initiator solution is dripped into the reaction container respectively, and the dripping is controlled to be completed within 1.5 to 2 hours.
[0033] The third aspect of the present invention provides the use of the transfer adhesive in laser transfer coating.
[0034] The beneficial effects of the present invention are:
[0035] The transfer adhesive of the present invention has a low emulsifier content in the raw materials for preparing the transfer adhesive, and a low dose of emulsifier is selected, which is similar to soap-free emulsion polymerization. In the synthesis process of traditional emulsions, more emulsifiers are used. During the film-forming process of this type of emulsion, small molecule emulsifiers will be dispersed in the coating in a non-homogeneous or tortuous state as the latex particles are demulsified, which directly leads to the coating being easy to form diffuse reflection during high-temperature molding, so that the laser effect is reduced when the transfer adhesive is used for laser transfer coating.
[0036] The transfer adhesive of the present invention is similar to a soap-free emulsion. A solid acrylic resin with a high acid value is selected as a protective adhesive for emulsion synthesis. The solid resin has good hydrophilicity and a high Tg, which makes the coating more uniformly distributed during the film-forming process. At the same time, the high Tg hydrophilic outer layer gives the coating surface better flatness, similar to a mirror effect. During high-temperature molding, it is easier to form mirror reflection and obtain a better laser effect.
[0037] The transfer adhesive of the present invention has good mechanical stability and good alcohol dilution resistance; the transfer adhesive of the present invention has obvious advantages for the needs of adding ethanol to reduce surface tension, improve leveling effect or increase the drying speed of the coating.
[0038] The transfer adhesive of the present invention can be regarded as a standard core / shell structure from the perspective of latex particle structure. The hard shell layer can give the coating better temperature resistance and withstand the test of high-temperature molding; the soft core layer that has undergone a certain degree of cross-linking gives the coating better film-forming effect and film-forming strength, and has better workability. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a finished product effect diagram of the transfer adhesive of Example 1 being applied as a laser transfer coating to an actual packaging product.
[0040] Figure 2 This is a finished product effect diagram of the transfer adhesive of Example 2 being applied as a laser transfer coating to an actual packaging product. DETAILED DESCRIPTION
[0041] The content of the present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples and comparative examples, unless otherwise specified, can be obtained from conventional commercial sources, or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art. The "parts" in the examples all refer to "parts by mass".
[0042] Example 1
[0043] This embodiment provides an environmentally friendly transfer adhesive, the raw materials and proportions are as follows:
[0044]
[0045] The acrylic monomers include:
[0046]
[0047] Note: Specific parameters of the selected solid acrylic resin: Mw: 8500; acid value (mgKOH / g): 215; Tg (℃): 85; the concentration of the ammonium persulfate aqueous solution is 10wt%.
[0048] This embodiment provides a method for preparing the transfer adhesive, and its production process is as follows:
[0049] (1) Add measured deionized water, solid acrylic resin and emulsifier into a reaction kettle, start stirring, set the stirring speed at 80 to 150 rpm, then add measured ammonia water, start heating, and set the temperature at about 85°C.
[0050] (2) After the temperature in the reactor rises to 85°C and the solid resin is completely dissolved, 60% of the measured initiator aqueous solution is added to the reactor at one time, and then the acrylic monomer and the crosslinking agent are mixed, and the remaining 40% of the initiator aqueous solution is added dropwise at the same time, and the dripping is controlled to be completed synchronously within 1.5 to 2.0 hours.
[0051] (3) After the acrylic monomer and the initiator are mixed and dripped simultaneously, the mixture is kept at 85° C. for 1 hour, then cooled to room temperature, and finally a measured amount of film-forming aid is added. After stirring for 30 minutes, the material can be discharged.
[0052] Example 2
[0053] This embodiment provides an environmentally friendly transfer adhesive, the raw materials and proportions are as follows:
[0054]
[0055] The acrylic monomers include:
[0056]
[0057] Note: Specific parameters of the selected solid acrylic resin: Mw: 8500; acid value (mgKOH / g): 215; Tg (℃): 85; the concentration of potassium persulfate aqueous solution is 12wt%.
[0058] This embodiment provides a method for preparing the transfer adhesive, and its production process is as follows:
[0059] (1) Add measured water, solid acrylic resin and emulsifier into a reaction kettle, start stirring, set the stirring speed at 80 to 150 rpm, then add measured ammonia water, start heating, and set the temperature at about 85°C.
[0060] (2) After the temperature in the reactor rises to 85°C and the solid resin is completely dissolved, 60% of the measured initiator aqueous solution is added to the reactor at one time, and then the acrylic monomer and the crosslinking agent are mixed, and the remaining 40% of the initiator aqueous solution is added dropwise at the same time, and the dripping is controlled to be completed synchronously within 1.5 to 2.0 hours.
[0061] (3) After the acrylic monomer and initiator are mixed and dripped simultaneously, the mixture is kept at 85° C. for 1 hour, then cooled to room temperature, and finally a measured amount of film-forming aid is added. After stirring for 30 minutes, the mixture can be discharged.
[0062] The transfer adhesive prepared in the above Examples 1 to 2 was subjected to a molding test, and the test method was as follows:
[0063] The sample was scraped onto a PET film using a 4 μm wire rod, and then compression molded at 150° C. with a compression time of 0.5 seconds and a compression pressure of 0.5 MPa.
[0064] The transfer adhesive prepared in the above Examples 1 to 2 was tested for glossiness, and the test method was as follows:
[0065] Use a 4μm wire rod to scrape the sample on offset black and white cardboard, and then use a 60-degree gloss meter to test it.
[0066] The molding test and gloss test results of Examples 1 and 2 are shown in Table 1 below:
[0067] Table 1
[0068] Test situation Example 1 Example 2 Molding 150℃ anti-sticking test Non-stick version Non-stick version Glossiness / 60 degrees 69 72
[0069] The transfer adhesives prepared in Examples 1 and 2 were applied as laser transfer coatings to actual packaging products, and the finished products were shown in the attached drawings. Figure 1 and attached Figure 2 The finished product of laser transfer coating produced by using the transfer adhesive has clear embossed patterns and distinct contours, and the laser effect is good, which meets the requirements of subsequent product use.
[0070] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A transfer adhesive, characterized in that: The raw materials for preparing the transfer adhesive include the following components in parts by weight: 45~65 parts of water, 8~18 parts of solid acrylic resin, 3~5 parts of ammonia water, 0.2~0.6 parts of emulsifier, 25~45 parts of acrylic monomer, 2~5 parts of initiator solution, 0.2~2 parts of crosslinking agent, 1~5 parts of film-forming aid; The solid acrylic resin has an acid value of 140-280 mg KOH / g and a Tg of 50-150° C.; The weight average molecular weight of the solid acrylic resin is 4000-30000; The acrylic monomer is a combination of a soft monomer and a hard monomer; the soft monomer includes at least one of methyl acrylate, ethyl acrylate, butyl methacrylate, butyl acrylate, isooctyl methacrylate, isooctyl acrylate, dodecyl acrylate, octadecyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, hydroxybutyl methacrylate, and isobornyl acrylate; the hard monomer includes at least one of styrene, methyl styrene, methyl methacrylate, isobornyl methacrylate, and ethyl methacrylate.
2. The transfer adhesive according to claim 1, characterized in that: The emulsifier is an anionic emulsifier.
3. The transfer adhesive according to claim 1, characterized in that: The copolymer of the acrylic monomer has a Tg of -5 to 10°C.
4. The transfer adhesive according to claim 1, characterized in that: The initiator solution is an aqueous solution of a thermal decomposition type free radical initiator; the concentration of the initiator solution is 5-30wt%.
5. The transfer adhesive according to claim 1, characterized in that: The crosslinking agent includes at least one of ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, N-hydroxymethyl acrylamide, and N,N'-methylenebisacrylamide.
6. The transfer adhesive according to claim 1, characterized in that: The film-forming aid includes at least one of ethylene glycol monobutyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol methyl ether, propylene glycol vinyl acetate, and dipropylene glycol methyl ether.
7. A method for preparing the transfer adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Add water, solid acrylic resin and emulsifier into a reaction vessel, stir, add ammonia water, and heat; (2) 50-70% of the initiator solution is added into the reaction container at one time, the acrylic monomer and the crosslinking agent are mixed and then the remaining initiator solution is added dropwise into the reaction container respectively, and the mixture is kept warm for 0.5-1.5 hours. The film-forming aid is added after the temperature is lowered, and the transfer adhesive is obtained by stirring.
8. Use of the transfer adhesive according to any one of claims 1 to 6 in laser transfer coating.
Citation Information
Patent Citations
Acrylate emulsion used for vacuum aluminum plating and laser embossing and preparation method thereof
CN102643380A
Water-soluble cigarette packet laser transferring glue and preparation method thereof
CN102838952A